Are rates of ageing determined in utero? - Sayer, A; Cooper, C; Evans, JR; Rauf, A; Wormald, R; Osmond, C; Barker, D (1998)
BACKGROUND: epidemiological studies have shown that poor early growth is associated with cardiovascular and other degenerative diseases. This has been explained by programming, whereby undernutrition and other influences which restrict early growth permanently change the structure and physiology of the body. The long-term effects of poor early nutrition on ageing have been demonstrated in animals but not studied in man. OBJECTIVES: to determine if poor early growth was associated with increased markers of ageing in later life. METHODS: we traced 1428 men and women, born in Hertfordshire between 1920 and 1930, for whom records of early weight were available. 824 (58%) were interviewed at home and 717 (50%) attended clinic for eye examination, audiometry, grip strength measurement, skin thickness ultrasound and anthropometry. RESULTS: lower weight at 1 year was associated with increased lens opacity score, higher hearing threshold, reduced grip strength and thinner skin. Visual acuity, macular degeneration and intraocular pressure were not related to early growth. CONCLUSIONS: the associations between early growth and markers of ageing suggest that in some systems, ageing may be programmed by events in early life. A potential mechanism is the impaired development of repair systems.